The Intraoperative Immunohistochemical Staining of CD56 and CK19 Improves Surgical Decision for Thyroid Follicular Lesions - Ju Yeon Pyo; Sung-eun Choi; Eunah Shin; JaSeung Koo; SoonWon Hong (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Background When differential diagnosis is difficult in thyroid follicular lesions with overlapping histological features, the immunohistochemical staining can help confirm the diagnosis. We aimed to evaluate the effectiveness of rapid immunohistochemical stains of CD56 and cytokeratin 19 on frozen sections of thyroid follicular lesion and explore the possible gains and limitations of the practice. Methods Eighty-six nodules of 79 patients whose intraoperative frozen sections were selected as the control group, and 53 nodules of 48 patients whose intraoperative frozen sections were subject to rapid immunohistochemistry were selected as the study group. Results Five nodules (6%) in the control group were diagnosed as follicular neoplasm and six nodules (7%) were deferred. In the study group, six nodules (11%) were follicular neoplasm and none were deferred. Three nodules (4%) in the control group showed diagnostic discrepancy between the frozen and permanent diagnoses, but none in the study group. The average turnaround time for the frozen diagnosis of the control group was 24 minutes, whereas it was 54 minutes for the study group. Conclusions Intraoperative rapid immunohistochemical stains significantly decreased the diagnostic discrepancy in this study. Considering the adverse effects of indefinite frozen diagnosis or discrepancy with permanent diagnoses, the intraoperative rapid immunohistochemical stain can help to accurately diagnose and hence provide guidance to surgical treatment.